Dinamika Sosioekonomi Pada Ilmu Ekonomi Islam Klasik - Rikmat Ismatullah (LITERASI (Jurnal Ilmu Pendidikan), 2009)
M. Umer Chapra discusses various concepts that related to the Islamic economic system and compare with the conventional economic  system,  directions  and  challenges  facing  the  Islamic  economy in the future as well as, as the central theme of his book, he picked up the concept of  Ibn  Khaldun's economic  development.  Interestingly,  he  managed  to  formulate  the  concept  into  a  cycle  that  is  easy  to  understand.He not only succeeded in formulating the concept of Ibn Khaldun into the cycle of increase progress and decrease cycles, but also he was able to further define the relationship between one component of development linkages with other components. Ibn  Khaldun  explains the important for  the development of Sharia  (S),  the development  community  (W),  law  enforcement  and  other  Development  (j & g),  as well as the role of  Government (G).   Umer  Chapra  formulate  these  components  in  the  cycle,  the   cycle   advances  toward  him:  SNW-j &  g-GS  and  other  cycle: j & g-WNSG-j & g. In this article, he discusses about some of the thinking of classical Islamic scholars who provide the base  foundation  in  the concept of Islamic  economics  in  particular  Ibn  Khaldun  in  his several works such as the Muqaddimah, which tried to  determine  factors  affecting  quality  by  analyzing  factors  such as the role  of interconnected moral factors, psychological, political, economic, social, demographic, and historical phenomena of the rise and fall of dynasties  and  civilizations.Keywords: Capra, Systems, Economics, Islam.